Writing Rhetorically Framing First Year Writing - Fontenot, Kirk; Rodrigue, Shelley; Waller, Wanda M. (Open textbook library.)
This course equips students with a strong understanding of how to use rhetorical modes that underpin much academic writing. The textbook covers modes related to creative writing, such as narration and illustration, while also covering analytically-focused modes such as comparison and cause and effect. Detailed assignment sheets are supplemented by helpful student worksheets for each major paper assignment. The book's final chapter includes grammar and style exercises. This textbook has been heavily adapted from material taken from English Composition I: Rhetorical Methods-Based, an OER developed and authored by Lumen Learning. Each chapter’s author has edited and created new content using Lumen Learning’s text as its primary source material, except where otherwise indicated. Where applicable, other source materials have been noted at the chapter level. This textbook was created as part of the Interactive OER for Dual Enrollment project, facilitated by LOUIS: The Louisiana Library Network and funded by a $2 million Open Textbooks Pilot Program grant from the Department of Education. This project supports the extension of access to high-quality post-secondary opportunities to high school students across Louisiana and beyond. This project features a collaboration between educational systems in Louisiana, the library community, Pressbooks technology partner, and workforce representatives. It will enable and enhance the delivery of open educational resources (OER) and interactive quiz and assessment elements for priority dual enrollment courses in Louisiana and nationally. Developed OER course materials will be released under a license that permits their free use, reuse, modification and sharing with others.The target audience for this project and this textbook are dual enrollment students. Dual enrollment is the opportunity for a student to be enrolled in high school and college at the same time. A dual enrollment student receives credit on both their high school and college transcripts for the same course